2007
DOI: 10.14310/horm.2002.1111025
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and leptin levels in obese adolescents. Relationship with body fat and insulin resistance

Abstract: ObJEctIVE: Ghrelin and leptin levels are influenced by body fat (bF%), pubertal stage and possibly insulin resistance (Ir). the aim of our study was: 1) to compare fasting ghrelin and leptin levels between obese and non-obese, adolescents, 2) to investigate possible correlations of these hormones with bF %, as well as Ir. DEsIGN: twenty obese insulin resistant (Ir) adolescents, twenty obese non Ir (NIr) and fifteen healthy non-obese, age-matched adolescents were studied. In all participants, height, weight, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
5
18
1
Order By: Relevance
“…Ghrelin levels have been shown to be down-regulated in obese individuals [25, 26] and to increase in response to diet- and/or exercise-induced weight loss [24], suggesting that ghrelin plays a role in the long-term regulation of energy balance. An increase in ghrelin levels secondary to weight loss can be seen as a compensatory mechanism to try to restore energy balance by upregulating hunger levels and ultimately energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin levels have been shown to be down-regulated in obese individuals [25, 26] and to increase in response to diet- and/or exercise-induced weight loss [24], suggesting that ghrelin plays a role in the long-term regulation of energy balance. An increase in ghrelin levels secondary to weight loss can be seen as a compensatory mechanism to try to restore energy balance by upregulating hunger levels and ultimately energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…It is during this interval that leptin increases to its maximum value postoperatively [14,22] . In nonobese adults the serum reference value of leptin is 11.6 8 1.3 ng/ml, but the leptin levels are influenced by the amount of body fat, age, gender and metabolic diseases such as diabetes mellitus [23,24] . We defined a low leptin serum level as a value of ^ 10 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, conflicting results have been reported [20,21]. Some reports suggested that ghrelin either stimulates [18,19,22] or inhibits insulin secretion depending on the experimental condition [23,24].…”
Section: Ghrelin Level Versus Insulin Levelmentioning
confidence: 99%